PENDIDIKAN NONGRADASI: PENGAKUANPERBEDAAN INDIVIDU - Sunardi Sunardi (Jurnal Cakrawala Pendidikan, 2008)
The objective of this researchis to develop a non-graded education model Inthis model, curriculum materials are adapted into sequentially arranged materials.Students aregrouped on the bases of their ages, it is possible to have a variety oflearning materialsand a variety of learning activities within one classroom at thesame time. An individual mastery learning approach is implemented. The locationof researchwas in the town of Surakarta. The initial activity was adapting theexisting curriculum materials into sequential learning units.The non~gradedmodelwas tried out in grade 1 of SO Al Firdaus with 62 students (parallel classes).Research results indicate: I)The initial levelsof competence of students in aclassroom are heterogeneous.2) In terms of language and sequence of materials,theadapted curriculum package was rated as excellent, but in appropriateness tothe levels of development, a few materials for lower gradesneed to be revised. 3)Teachers and parents agreed on the heterogeneity of classes in schools, butdisagreed on the feasibility of multilevel curriculum materials and multi-modalityof learning. Thetwo groups also agreed on the low competence of teachers inteaching non-graded classrooms. 4) After one year in progress, the non-gradedmodel showed beneficial for fast and slow learners